2001
DOI: 10.1007/s002640100247
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological support for a multifactorial aetiology of Kashin-Beck disease in Tibet

Abstract: We carried out a cross-sectional study in 12 rural villages in order to identify the risk factors for Kashin-Beck disease in Tibet. Children aged 5-15 years (n=575) were examined and their corresponding houses were visited. Samples were collected in order to study fungal contamination of stored grain and the organic matter content of drinking water. Multivariate analysis was performed using logistic regression and population attributable fractions were computed to estimate the impact of each factor. The follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 13 publications
1
53
0
3
Order By: Relevance
“…A variety of hypotheses (Fang 1988;Zamana 1995;Chasseur et al 1997;La et al 2001;Chasseur et al 2001;Suetens et al 2001) have been proposed since 1849 when the disease was first discovered in Russia. Selenium deficiency in the environment, organic matter in drinking water, and fungal contamination in stored grains or food are three dominating opinions on the etiology of KBD (Tan et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of hypotheses (Fang 1988;Zamana 1995;Chasseur et al 1997;La et al 2001;Chasseur et al 2001;Suetens et al 2001) have been proposed since 1849 when the disease was first discovered in Russia. Selenium deficiency in the environment, organic matter in drinking water, and fungal contamination in stored grains or food are three dominating opinions on the etiology of KBD (Tan et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…the so-called selenoproteins [28]. The adverse effects caused by selenium deficit and most frequently described in literature include dilated cardiomyopathy (Keshan disease) and endemic osteoarthropathy (Kashin-Beck disease) [28][29][30].…”
Section: The Issue Of Selenium Deficitmentioning
confidence: 99%
“…The mean serum Se level increased steadily to a non-endemic level in 2000 and attained the highest level in 2005. Two studies conducted in Lhasa Prefecture, an Se-and iodine-deficient area in Tibet, reported that 49 % of 280 subjects had Kashin-Beck disease (67) and all had severe Se deficiency (27) . There was also high Se deficiency rate (83 %) in 120 children aged 6-14 years in Shaanxi Province (93) .…”
Section: Zincmentioning
confidence: 99%
“…Keshan disease, a congestive cardiomyopathy, is recognised to be associated with Se deficiency (23) and is endemic in China (24) . Se deficiency is also implicated in Kashin-Beck disease (osteochondropathy) (25) although iodine deficiency is considered common in this disease (26,27) . Ca is required to maintain the rigidity and strength of bones to prevent osteoporosis (28) .…”
mentioning
confidence: 99%